Effect of Silver Nanoparticles on the Optoelectronic Properties of Graphene Oxide Films - Э. Алихайдарова; Е. Селиверстова; Н. Ибраев (Қарағанды университетінің хабаршысы. Физика сериясы)
The effect of Ag nanoparticles (NPs) on the optical and optoelectronic properties of films based on graphene oxide has been studied. In the presence of Ag NPs, the morphology, as well as the thickness of graphene oxide films, were not changed. When Ag NPs were added, a change in the shape and position of the absorption bands and Raman spectra of graphene oxide was observed. It is shown that with the addition of Ag NPs, the G band of graphene oxide shifts to low frequencies, which may be the result of the absence of separate double bonds, while the ID/IG ratio was not changed, as did the number of Gr layers. In the absorption spectrum of the films, along with the absorption band of graphene oxide, a shoulder was registered, which can be associated with the absorption of Ag NPs. The optical density of Gr films with plasmonic NPs is higher than without them. Measurements of the optoelectronic characteristics showed that, in the presence of Ag NPs, an increase in the values of the photocurrent of graphene oxide is observed. The sensitivity of graphene oxide films was increased by almost 20 times when plasmonic NPs were added to them, and the detection ability increased by 25 times. The results obtained can be used in the development of new photosensitive devices for optoelectronic and applications.